Rut - Palmisano, Maria Carmela (Edinost in dialog, 2023)
This contribution, within the framework of the research project on values in JudeoChristian sources and traditions, aims to highlight the multiplicity of values which the figure of Ruth carries in the book dedicated to her. Looking at the plot of the narration, one can see how the theme of values, starting from Ruth, broadens and is present in the other protagonists of the narration, particularly in Boaz. After having presented the most relevant features of Ruth character that define her as »woman of valor«, the article considers the need to place the narrative in the biblical canon, mentioning particularly the Jewish one, without ignoring the specificities of the positioning of the narration within the Greek and Latin canon and in the different Christian confessions. The contribution shows how the figure of Ruth in the Jewish canon is closely connected to the two books that precede (Proverbs) and follow (Song of Songs) the story dedicated to her and how the canonical position enables a better understanding of the value system transmitted by the three texts and their message.
Keywords: Biblia; canon; darežljivost; emptiness; foreigner; friendship; fullness; generosity; Interpretacija; kanon; levirate law; ljubezen; love; Moabite; Moabka; polnost; praznina; Pregovori; prijateljstvo; Proverbs; Ruta; Ruth; Song of Songs; svaško pravo; tujka; Visoka pesem; vrla žena; woman of value